HUBUNGAN KEBIASAAN SARAPAN PAGI DAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI ANAK DI SD NEGERI 1 PANGKAJENE KABUPATEN SIDRAP - Sunarto; Nurul Fauziyah (Media Gizi Pangan, 2023)
In supporting the physical and development of children, various kinds of nutrients are needed in sufficient quantities to meet good development and growth, because the role of nutrition determines the state of children's health, including nutritional status. Skipping breakfast causes a nutritional deficit and cannot be replaced by nutrient intake through other meals. Intake of nutrients will affect the concentration and intelligence of children in receiving knowledge at school. The purpose of this study was to determine the relationship between breakfast habits and intake of macronutrients with the nutritional status of children at SD Negeri 1 Pangkajene, Sidrap Regency. This type of research uses a cross-sectional design. Population of elementary school students grades IV, V, IV. The sample in the study was 65 children. Breakfast habits were collected through a questionnaire. Intake of macronutrients is known through food recall interviews. Nutritional status is known through the value of BMI. Statistical test with Chi-Square. The results showed good breakfast habits (70.8%), adequate energy intake (95.4%), sufficient protein intake (90.8%), sufficient fat intake (92.3%), sufficient carbohydrate intake (96. 9%), normal nutritional status (61.5%). Statistical analysis found that there was a relationship between breakfast habits and intake of macronutrients with the nutritional status of children with a P value <0.05. The conclusion of this study is that there is a relationship between breakfast habits and intake of macronutrients with the nutritional status of children at SD Negeri 1 Pangkajene, Sidrap Regency. It is recommended for students to improve breakfast habits and pay more attention to the food they will consume